2017
DOI: 10.1007/s00415-016-8384-9
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of gender in Parkinson’s disease: a review

Abstract: Since the official and systematic inclusion of sex and gender in biomedical research, gender differences have been acknowledged as important determinants of both the susceptibility to develop neurodegenerative diseases in general population and the clinical and therapeutic management of neurodegenerative patients. In this review, we gathered the available evidence on gender differences in Parkinson's disease (PD) regarding clinical phenotype (including motor and non-motor symptoms), biomarkers, genetics and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
155
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 134 publications
3
155
1
5
Order By: Relevance
“…8 One potential explanation offered for this finding is that women are more likely to be risk-averse and therefore less likely to undergo a surgical procedure than men. 9 Our finding that men had lower PDQ-39 scores, and therefore better quality of life compared to women at the time of surgery, suggests that for women the risk of surgery was offset by the potential benefit only when their disease-related quality of life was comparatively worse.…”
Section: Discussionmentioning
confidence: 99%
“…8 One potential explanation offered for this finding is that women are more likely to be risk-averse and therefore less likely to undergo a surgical procedure than men. 9 Our finding that men had lower PDQ-39 scores, and therefore better quality of life compared to women at the time of surgery, suggests that for women the risk of surgery was offset by the potential benefit only when their disease-related quality of life was comparatively worse.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have revealed that male sex is a prominent risk factor for developing Parkinson's disease (PD) . At symptom onset, male PD patients are more likely to present with axial impairment when compared to female patients . Conversely, as the disease progresses, female PD patients seem to be at higher risk to develop treatment‐related motor complications .…”
mentioning
confidence: 99%
“…1 At symptom onset, male PD patients are more likely to present with axial impairment when compared to female patients. 2,3 Conversely, as the disease progresses, female PD patients seem to be at higher risk to develop treatment-related motor complications. 4,5 Indeed, it has been shown that prevalence of wearing-off is higher in female than in male PD patients.…”
mentioning
confidence: 99%
“…Consequently, a decline in the release of striatal dopamine (DA) leads to motor manifestations of PD involving resting tremor, bradykinesia, postural instability, and rigidity. Whether there is a sex difference concerning the risk for PD is controversial [2,3,4], but the beneficial effect of estrogen has been well-described in both culture and animal models of PD [5,6,7]. Hormone therapy with estrogens in humans has often been associated with serious side effects, especially after long-term exposure such as for treating breast cancer and blood clots [5].…”
Section: Introductionmentioning
confidence: 99%